Including a luminous central remnant in radiative transfer simulations for type Iax supernovae - Callan, Fionntan P.; Sim, Stuart; Collins, Christine E.; Shingles, Luke J.; Lach, Florian; Röpke, Friedrich; Pakmor, Rüdiger; Kromer, Markus; Srivastav, Shubham (Monthly notices of the Royal Astronomical Society, 2024)
Type Iax supernovae (SNe Iax) are proposed to arise from deflagrations of Chandrasekhar mass white dwarfs (WDs). Previous deflagration simulations have achieved good agreement with the light curves and spectra of intermediate-luminosity and bright SNe Iax. However, the model light curves decline too quickly after peak, particularly in red optical and near-infrared (NIR) bands. Deflagration models with a variety of ignition configurations do not fully unbind the WD, leaving a remnant polluted with 56Ni. Emission from such a remnant may contribute to the luminosity of SNe Iax. Here we investigate the impact of adding a central energy source, assuming instantaneous powering by 56Ni decay in the remnant, in radiative transfer calculations of deflagration models. Including the remnant contribution improves agreement with the light curves of SNe Iax, particularly due to the slower post-maximum decline of the models. Spectroscopic agreement is also improved, with intermediate-luminosity and faint models showing greatest improvement. We adopt the full remnant 56Ni mass predicted for bright models, but good agreement with intermediate-luminosity and faint SNe Iax is only possible for remnant 56Ni masses significantly lower than those predicted. This may indicate that some of the 56Ni decay energy in the remnant does not contribute to the radiative luminosity but instead drives mass ejection, or that escape of energy from the remnant is significantly delayed. Future work should investigate the structure of remnants predicted by deflagration models and the potential roles of winds and delayed energy escape, as well as extend radiative transfer simulations to late times.